2021
DOI: 10.1021/acscatal.1c01939
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cuprous Centers Supported on a Titanium-Based Metal–Organic Framework Catalyze CO2 Hydrogenation to Ethylene

Abstract: Hydrogenation of carbon dioxide (CO 2 ) to ethylene (C 2 H 4 ) can be achieved in two routes via tandem reactions: (1) CO 2 hydrogenation to methanol (CH 3 OH) followed by methanol-to-olefin conversion and (2) reverse water-gas shift reaction followed by Fischer−Tropsch synthesis. Here we present another tandem route for CO 2 -to-C 2 H 4 conversion via (3) CO 2 hydrogenation to ethanol (C 2 H 5 OH) followed by C 2 H 5 OH dehydration. Multiple cuprous (Cu I ) centers were loaded onto the Ti 8 (μ 2 -O) 8 (μ 2 -O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…388,407,416,417,430 In addition, some new approaches for the tandem process should be mentioned. Hydrothermal conversion of CO 2 to ethanol with further dehydration of the latter was proposed in the work of Zeng 431 et al The authors used copper catalyst introduced into the structure of Ti-based MOF MIL-125-NH 2 and reached the 90% selectivity to ethylene at 100 1C. They found that copper-based centres converted CO 2 to ethanol, while titanium-based ones were more efficient in the EtOH dehydration to ethylene.…”
Section: Methanol-mediated Co and Co 2 Hydrogenationmentioning
confidence: 99%
“…388,407,416,417,430 In addition, some new approaches for the tandem process should be mentioned. Hydrothermal conversion of CO 2 to ethanol with further dehydration of the latter was proposed in the work of Zeng 431 et al The authors used copper catalyst introduced into the structure of Ti-based MOF MIL-125-NH 2 and reached the 90% selectivity to ethylene at 100 1C. They found that copper-based centres converted CO 2 to ethanol, while titanium-based ones were more efficient in the EtOH dehydration to ethylene.…”
Section: Methanol-mediated Co and Co 2 Hydrogenationmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), as a type of functional materials crocheted from inorganic secondary building units (SBUs) and organic linkers, have attracted the attention of many scholars because of their various applications in a range of areas, such as multitype heterogeneous catalysis, , gas separation storage, , drug sustained release, fluorescent sensor and probe, , etc. So far, burgeoning reticular chemistry is a mature guide for the wise design and synthesis of crystalline porous MOFs with overall structure and chemical functionality, which could directly guide our understanding of the current generation of porous materials to design next-generation porous materials. Essentially, the modular idea in total metal–organic synthesis promotes the construction of different target MOFs by changing building blocks and coordination-assembly sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of MIL-125 as the support was critical to the tandem CO 2 -to-C 2 H 4 transformation: (1) the Ti 8 (μ 2 -O) 8 (μ 2 -OH) 4 SBU rather than other SBUs stabilized Cu I to avoid Cu 0 formation; (2) the short Cu I –Cu I distance in Ti 8 (μ 2 -O) 8 (μ 2 -O-CuI) 4 enhanced the synergistic effect on C 2 formation; (3) the strong Lewis acid Ti IV catalyzed C 2 H 5 OH dehydration at low temperatures (∼100 °C); and (4) C 2 H 5 OH was easily adsorbed on the Ti 2 (μ 2 -O–M + ) site in Ti 8 (μ 2 -O) 8 (μ 2 -O–CuI) 4 , which further induced β-elimination to produce C 2 H 4 ( Figure 9 b,c). This work highlighted new opportunities in using MOFs as novel supports for CO 2 hydrogenation to C 2 H 4 [ 126 ]. Moreover, this study indicated the pore-dependent activity and selectivity during CO 2 hydrogenation in tunable and ordered structure MOFs.…”
Section: Confined Synthesis and Confinement Effects Of Mofs As Host M...mentioning
confidence: 99%